Managing Women's Village Activists Participation in Village Development Planning - Andy Fefta Wijaya; Dian Andryanto; Wike Wike (Universitas Sultan Ageng Tirtayasa, 2020)
Decentralization of Indonesian villages provides opportunities for grassroots-level groups to participate in village development. This study explores the participation of women affiliated with women’s groups in the participatory processes of village development planningin the villages of Central Java. Using a mixed-methods strategy, this study found that many members of women’s groups known as women’s village activists have been involved in participatory planning processes, and used the processes to demand programs that improve women and family well-being. Besides, their priority for village development seems to differ from that of the current trend, which heavily focuses on village-scale infrastructure development. On average, this group of women have relatively good levels of education and have been active in community activities. The findings of this study reinforce the argument that women village activists who are quite active in community and grassroots activities are potential representatives in determining the priority of village development.